Examination of fertility measures from the 1992 and 2000 Malawi demograph and health surveys : a review of declining fertility - Mijoni, Bernard A (Department of Philosophy, 2024)
This thesis examines fertility measures from the 1992 and 2000 Malawi Demographic Health Surveys (DHS). There is evidence that fertility decline in Malawi has begun. This project further explores the associated change (if any) in family formation in response to the recorded fall in fertility. Cohort-period fertility rates, parity progression ratios and projected B60s are calculated in order to provide additional information on changes in women's preference for larger family sizes. These techniques have been selected to provide additional insight into the changing behaviour of women with regard to preference for larger family sizes. The cumulated cohort-period rates in the 2000 DHS show evidence of falling fertility. Declining trends at higher births orders are observed in the 2000 DHS among younger age groups, indicating recent fall in fertility. However, there is minimal evidence of declining fertility in the 1992 DHS or among rural-based women in general. In a scenario where fertility has started declining, a broadened approach to its measurement, such as the use of B60s, assists in providing information for evaluating previous fertility estimates and determining future directions in Malawi fertility